Controllable synthesis of TiO2 nanoparticles employing substrate/dielectrophoresis/sol‐gel. Issue 1 (18th November 2015) - Cui, Chenyang; Chen, Huiying; Zuo, Tongtong; Fu, Xiaotao; Chen, Lizhen; Geng, Junfeng; Li, Hua; Xing, Xuan
Abstract : The substrate/dielectrophoresis/ sol‐gel method can promote the compact and regular growth of TiO2 nanorods, while enhancing the catalytic activity for degradation of methyl orange. Abstract : Due to size‐dependent catalytic selectivity, the size and special morphology are of great importance to applications of TiO2 . The synthesis method of size and morphology control has been in need of innovation. In this study, TiO2 nanoparticles(TiO2 ‐NPs) with well‐defined morphology and homogenous size were synthesized using a novel method, in which bamboo substrate, dielectrophoresis (DEP) technology and a sol‐gel process were combined(substrate/ DEP/ sol‐gel). Powder X‐ray diffraction (XRD) and scanning electron microscopy (SEM) techniques were used to characterize the TiO2 ‐NPs. Further study showed that, with this combined method, the size and the uniformity of TiO2 ‐NPs can be controlled by changing the voltage of DEP. The number and arrangement of TiO2 nanorods can be controlled by changing the voltage. Substrate/ DEP/ sol‐gel proved to be an efficient way to form special morphologies of TiO2 ‐NPs. A visible‐light catalytic activity experiment showed that among three preparation methods, the substrate/ DEP/ sol‐gel method made TiO2 ‐NPs with the highest catalytic activity for degradation of methyl orange. TiO2 ‐NPs produced by the DEP/ sol‐gel process presented higher catalytic activity than TiO2 ‐NPs produced by only a sol‐gel process.